2021
DOI: 10.1186/s12954-021-00538-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of non-fatal overdose among people who use drugs: findings from rapid assessments in Massachusetts, 2017–2019

Abstract: Background People who experience non-fatal overdose (NFOD) are at high risk of subsequent overdose. With unprecedented increases in fentanyl in the US drug supply, many Massachusetts (MA) communities have seen a surge in opioid-related overdoses. The objective of this study was to determine factors associated with lifetime and past year NFOD in at-risk MA communities. Methods We conducted multiple rapid assessments among people who use drugs (PWUD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Individuals who dropped out of the program had overdosed in the past more than those who were retained, suggesting that individuals with an extensive history of substance use may need additional support maintaining engagement in an outpatient program. A recent study found individuals who experienced a non-fatal overdose were at increased risk of successive overdose and were more likely to engage in polysubstance use [ 20 , 21 ]. Moreover, polysubstance use may contribute to lifetime prevalence of overdose.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who dropped out of the program had overdosed in the past more than those who were retained, suggesting that individuals with an extensive history of substance use may need additional support maintaining engagement in an outpatient program. A recent study found individuals who experienced a non-fatal overdose were at increased risk of successive overdose and were more likely to engage in polysubstance use [ 20 , 21 ]. Moreover, polysubstance use may contribute to lifetime prevalence of overdose.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, RA methods have mostly been applied in low-income countries and humanitarian settings involving displaced communities [ 31 – 33 ]. In the last decade, a few studies deployed the methodology likewise in high-income settings [ 34 , 35 ]. These methods have been proven to gather knowledge about sensitive topics, such as substance use or HIV, whose affected populations might be difficult to involve in research [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…We classi ed population size as urban (> 50,000), metro (< 50,000 but within large metro area), and non-metro/rural (less than 25,000 and not within large metro area). Finally, we classi ed overdose rates (de ned as fatal opioid overdoses per 100,000 population in 2021) as very high (50-69), high (40-49), average (30-39) or lower (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) relative to all participating sites. While monthly monitoring to obtain indicator data occurred at all sites, more in-depth evaluation involving semi-structured interviews, eld observations, and site visits occurred only at 12 selected sites.…”
Section: Evaluation Designmentioning
confidence: 99%
“…8, 9 The purity of substances and amount of fentanyl contaminants are unpredictable, thus contributing to fentanyl's prominent role in drug-related morbidity and mortality. [10][11][12] These factors combined have led to a dangerously high risk of overdose among people who use drugs (PWUDs); in a rapid assessment conducted between 2017 and 2019 with 469 PWUDs in the state of Massachusetts, 36.9% reported a past-year nonfatal overdose event 13 .…”
Section: Introductionmentioning
confidence: 99%